Rancangan Media Pembelajaran Biologi Kelas XI Berbasis Augmented Reality di MAN 2 Agam - Annisa, Sherly; Efriyanti, Liza; Zakir, Supratman; Supriadi, Supriadi (Indonesian Research Journal on Education, 2022)
This research was conducted from the problems found after observations at MAN 2 Agam found the problem that students and teachers only rely on manual learning and still use printed books without using learning media. So that teachers only use simple tools in teaching and learning activities that make students bored and less interested in repeating the material that has been explained about the "human motion system". Therefore, the authors design Augmented Reality-based learning media in order to increase student interest in learning, while the purpose of this is to produce a valid, practical and effective Augmented Reality-based learning support media design. The method used in this study is the Research and Development (R&D) method using the Luther-Sutopo version of the MultimediaDevelopment Life Cycle (MDLC), which consists of six stages, namely concept (conception), design (design), material collection (material collection), assembly (manufacture), testing (testing) and distribution (distribution). And there are three product tests carried out in this study, namely the validity test given to lecturers of field experts or experts in the field of study, practicality tests carried out by biology subject study teachers and effectiveness tests given to students at MAN 2 Agam class XI. Based on the results of the product test that has been carried out by the author of the validity test, the average value is 0.94 which is declared valid, and for practicality obtained the average value is 0.76 which is declared practical and for the effectiveness test, the average value is - the average is 0.97 which is declared effective.